Real-time visualization of phagosomal pH manipulation by Cryptococcus neoformans in an immune signal-dependent way - Santiago-Burgos, Emmanuel J.; Stuckey, Peter V.; Santiago-Tirado, Felipe H. (Frontiers in Cellular and Infection Microbiology, 2022)
Understanding of how intracellular pathogens survive in their host cells is important to improve management of their diseases. This has been fruitful for intracellular bacteria, but it is an understudied area in fungal pathogens. Here we start elucidating and characterizing the strategies used by one of the commonest fungal pathogens, Cryptococcus neoformans, to survive intracellularly. The ability of the fungus to survive inside host cells is one of the main drivers of disease progression, yet it is unclear whether C. neoformans resides in a fully acidified, partially acidic, or neutral phagosome. Using a dye that only fluoresce under acidic conditions to stain C. neoformans, a hypha-defective Candida albicans mutant, and the nonpathogenic Saccharomyces cerevisiae, we characterized the fungal behaviors in infected macrophages by live microscopy. The main behavior in the C. albicans mutant strain and S. cerevisiae-phagosomes was rapid acidification after internalization, which remained for the duration of the imaging. In contrast, a significant number of C. neoformans-phagosomes exhibited alternative behaviors distinct from the normal phagosomal maturation: some phagosomes acidified with subsequent loss of acidification, and other phagosomes never acidified. Moreover, the frequency of these behaviors was affected by the immune status of the host cell. We applied the same technique to a flow cytometry analysis and found that a substantial percentage of C. neoformans-phagosomes showed impaired acidification, whereas almost 100% of the S. cerevisiae-phagosomes acidify. Lastly, using a membrane-damage reporter, we show phagosome permeabilization correlates with acidification alterations, but it is not the only strategy that C. neoformans uses to manipulate phagosomal acidification. The different behaviors described here provide an explanation to the confounding literature regarding cryptococcal-phagosome acidification and the methods can be applied to study other intracellular fungal pathogens.